EFEKTIVITAS METODE KISAH DALAM PEMBELAJARAN AKIDAH AKHLAK DI MADRASAH ALIYAH - Khoesnan, Farid (CV. Amerta Media, 2018)
Learning is strongly influenced by several components namely educators, learners, learning materials, learning methods, infrastructure and environmental advice. Methods in education have a very important position for the achievement of goals, because without the method of learning materials can not be processed effectively. Among the methods that are effective in education on the subjects of Akidah Akhlak is the story method. In this method the technique used is to reveal historic events originating from the Qur'an that contain the value of moral, spiritual, and social education, both on stories of good nature, and injustice. This research is a qualitative research whose main source is data related to Learning of Akidah Akhlak in MAN 2 Banyumas. The data obtained by doing observation, interview and documentation. The collected data is then analyzed. The results showed that Application of Acts Method In Learning Akidah Morals in MAN 2 Banyumas is one form of variation methods and is expected to help educators in the learning process to make it easier in delivering the subject matter. The story method is very effective because students are more enthusiastic and easy to understand the material during the learning process takes place.Key Words: Effectiveness, Story Method, Akidah Akhlak Learning